2021
DOI: 10.1590/1980-220x-reeusp-2020-0578
|View full text |Cite
|
Sign up to set email alerts
|

Spatial analysis of congenital syphilis in the State of Rio Grande do Norte, between 2008 and 2018

Abstract: Objective: To analyze the spatial distribution of congenital syphilis cases in a state in northeastern Brazil. Method: This is an ecological study, with secondary data for the period from 2008 to 2018, taking as a sample the notified cases of congenital syphilis in Rio Grande do Norte. In the data analysis, the eight health regions of the state were used as units of analysis, and the local and global Moran’s I was performed, with subsequent smoothing through the local empirical Bayesian method, which resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…High-high patterns observed in coastal regions of the Northeast may be associated with the population context and great availability of healthcare services and maternity hospitals, resulting in increased notifications. In contrast, low-low patterns in the central region of the Northeast may be associated with the expansion of the Family Health Strategy program in recent years, suggesting effective prevention measures during prenatal care ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…High-high patterns observed in coastal regions of the Northeast may be associated with the population context and great availability of healthcare services and maternity hospitals, resulting in increased notifications. In contrast, low-low patterns in the central region of the Northeast may be associated with the expansion of the Family Health Strategy program in recent years, suggesting effective prevention measures during prenatal care ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al ( 36 ) showed that several Brazilian cities lacked rapid tests for syphilis, reducing diagnosis, treatment, and control of syphilis in the population. Furthermore, some Brazilian regions should restructure the laboratory network to perform treponemal and nontreponemal tests ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“…New strategies are needed to reduce syphilis transmission, such as spatial analysis, which has previously been applied in syphilis-related research [ 10 , 14 , 15 , 19 ]. However, due to a lack of studies, how and to what extent this tool is being used is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In Africa, the implementation of self-tests for HIV and syphilis in men's workplaces can be thought of as an approach to increase the availability of and access to tests among men and provide linkage to treatment and prevention services [18]. New strategies are needed to reduce syphilis transmission, such as spatial analysis, which has previously been applied in syphilis-related research [10,14,15,19]. However, due to a lack of studies, how and to what extent this tool is being used is unclear.…”
Section: Introductionmentioning
confidence: 99%